Closure - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2021)
JIFAM, Vol.3, Issue 1, March 2021Framework for Facilities Management Services Procurement in Public Buildings in Abuja-NigeriaSani Momoh, Jennifer Ayegba, Luqman Oyewobi, Calistus Ayegba, Abdulquadri Bilau & Richard JimohHydropower Sustainability Assessment Protocol (HSAP) Implementation in Indonesia: A mini-reviewNovi Andriany Teguh & Ainul Firdatun NisaaWeighting The Fire Protection Systems Technical Requirements to Determine Flats ReliabilityAgainst Fire HazardsAris Aminulwahyu, I Putu Artama Wiguna & Tri Joko Wahyu AdiPurabaya Bus Station Service Performance in New Adaptation PeriodPutu Cinthya Pratiwi Kardita, Achmad Wicaksono & M. Ruslin AnwarModeling and Optimization of the Compressive Strength of High Volume Fly Ash ECC with Low Modulus PVA Fiber Using Response Surface Methodology (RSM)Isyaka Abdulkadir & Bashar S. MohammedImplementation of Risk Management in Property ProjectsI Wayan Muka & Agung WibowoA New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in IndonesiaFarrell Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert WicaksonoJIFAM, Vol.2, Supplement 1, December 2020Life Cycle Cost Structure of a Government Office Green Building – Case of the Ministry of Public Works and Housing Main BuildingDomenico Adi Nugroho, Hitapriya Suprayitno, Tri Joko Wahyu AdiEffect of Waste Tire Rubber on the Durability Behavior of Cement Composites: A ReviewIsyaka Abdulkadir, Bashar S. MohammedPreliminary Reflection on Basic Principle of Operation Management for Public Work Infrastructure Asset ManagementRia Asih Soemitro, Hitapriya SuprayitnoComparing the Result of Infrastructure and Facility Demand Distribution Similarity Test Between Using Percentage Value and Real ValueHitapriya Suprayitno, Vita Ratnasari, Ria Asih Aryani SoemitroLearn Asset Management based on PTPN 9 Case – Preliminary Overview of the Institution, the Function, and the General Business AssetsSoedarmawan Soewardi, Hitapriya Suprayitno, Ria Asih Aryani Soemitro